2022
DOI: 10.1021/acsnano.2c00129
|View full text |Cite
|
Sign up to set email alerts
|

Low-Tortuosity Thick Electrodes with Active Materials Gradient Design for Enhanced Energy Storage

Abstract: The ever-growing energy demand of modern society calls for the development of high-loading and high-energy-density batteries, and substantial research efforts are required to optimize electrode microstructures for improved energy storage. Low-tortuosity architecture proves effective in promoting charge transport kinetics in thick electrodes; however, heterogeneous electrochemical mass transport along the depth direction is inevitable, especially at high C-rates. In this work, we create an active material gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 26 publications
2
45
0
Order By: Relevance
“…Wu et al recently reported a low‐tortuosity electrode with an AM gradient using a phase‐inversion process under a magnetic field. [ 65 ] LFP decorated with superparamagnetic iron oxide (Fe 3 O 4 ) nanoparticles could be elevated by a magnet along the thickness direction in the slurry, which was then submerged into the nonsolvent to complete the phase‐inversion process. The gradient composition distribution was confirmed by both SEM and nano‐CT images (Figure 4c).…”
Section: Gradient Design In Cathodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al recently reported a low‐tortuosity electrode with an AM gradient using a phase‐inversion process under a magnetic field. [ 65 ] LFP decorated with superparamagnetic iron oxide (Fe 3 O 4 ) nanoparticles could be elevated by a magnet along the thickness direction in the slurry, which was then submerged into the nonsolvent to complete the phase‐inversion process. The gradient composition distribution was confirmed by both SEM and nano‐CT images (Figure 4c).…”
Section: Gradient Design In Cathodesmentioning
confidence: 99%
“…Recently, ice-templating and phase inversion have been demonstrated to produce low-tortuosity thick electrodes with gradient porosity or composition, which proves effective in further accelerating reaction kinetics. [41,42,65] More extensive approaches beyond the above are required to accurately control architecture in low-tortuosity electrodes, and the interplay between microstructure and properties should be carefully evaluated to provide further guidance for advanced battery design.…”
Section: Engineering Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28–31 ] According to the diffusion coefficient equation (Deff=D×ετ)$\left( {{D_{{\rm{eff}}}} = D \times \frac{\varepsilon }{\tau }} \right)$ (ε is porosity and τ is tortuosity), the conductive pathways is decided by the ε and τ. [ 32–34 ] The randomly arranged structures of 3D thick electrodes possess high tortuosity, prolonging the electron transport path and ion diffusion pathway, resulting in the local polarization of the electric field and lithium‐ion flux inside the electrode. [ 32,35 ] Besides, the high tortuosity would cause the Li plating merely occur at circumscribed anode/electrolyte interfaces, giving rise to inferior rate performances (<1 mA cm −2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The parameter j lim mainly depends on the value of β, which is increased in thicker electrodes with a smaller porosity and a higher tortuosity. , Therefore, architectural design in thick electrodes is pursued to remain a less tortuous structure and a shorter lithium-ion pathway . Recently, tremendous research efforts have been made in the structural design of thick electrodes, such as vertically arranged pores, , gradient pore structure, , and gradient active material, , with various advanced fabrication methods, such as ice templating, ,, phase inversion, ,,, and solvent evaporation . Although the above design strategies can promote the mass transport kinetics by creating pores and channels inside the thick electrodes, a high porosity is often employed.…”
Section: Introductionmentioning
confidence: 99%